Análise da sustentabilidade do desenvolvimento em Mato Grosso - Santos, Nagela Bueno dos (2017)
The search for a broad understanding of the development of societies, their constitutive and determining factors, has led to the emergence of several theories and models. Increasingly complex answers were given to the question: what is development? Efforts to obtain a measure that represented the complexity of concepts were also increasing. In addition to economic viability, the development models began to be analyzed by institutional aspects, social relevance and ecological prudence. From this perspective, the central theme of this research is the proposal of a more realistic view on the development of the municipalities of Mato Grosso. It was sought to identify how the adoption of a more complex index could affect the classification of the standard of living in the municipalities of Mato Grosso. Firstly, the constitutive factors of the development trajectory of the state were identified, as well as the most relevant aspects of the current model were characterized. Then, an index of municipal development was adapted so that its application resulted in a measure closer to the real level of development achieved in the state. Based on this characterization and the application of the index, the development of the municipalities of Mato Grosso was analyzed in order to identify possible social, economic and environmental disturbances that could compromise the quality of life of current and future generations. The Sustainability Index of the Municipalities of the Amazon (ISMA) was used as a methodological basis, with the proposal to include new specific indicators, as well as an adaptation to the calculation method (Adjusted ISMA). It is assumed that this adaptation in the index could provide a more reliable view of the level of development of the municipalities of Mato Grosso and significantly affect their classification in relation to other indicators, especially in relation to the IDH-M and per capita income . Research on the constitutive factors of Mato Grosso's development trajectory revealed that the coordinating action of governments since the 1960s was decisive in laying the foundations and consolidating agribusiness as the basis of the current model, starting in 1995. In this sense, policies Public policies were oriented according to the objectives defined for the country's macroeconomic indicators rather than the adoption of policies that prioritize the broadening of individuals' opportunities. As a result, the application of the adjusted ISMA proved that, in fact, the adoption of a more complex index significantly changes the classification of development of the municipalities, with some improving and others worsening its classification. In general, the Adjusted ISMA showed a more pessimistic scenario of development in Mato Grosso compared to other indicators. The factors that contributed the most to this scenario were economic and political-institutional. This result was a reflection of the political and economic institutions formed in the phase of constitution of the current model of development that still could not be overcome.